PATTERN OF ANTIBIOTIC SUSCEPTIBILITY OF COMMON ISOLATES IN ICU OF A TERTIARY CARE HOSPITAL: 2 YEARS STUDY - Chakraverti, Trinain Kumar; C Tripathi, Purti (International Journal of Clinical and Biomedical Research, 2015)
Introduction: Antibiotic resistance is a major emerging world-wide problem in the intensive care unit (ICU). The aim of this study was to study the antimicrobial resistance pattern of microbial isolates from patients in intensive care units (ICUs). Material and methods: All isolates from different clinical samples were collected and processed by standard microbiological techniques. Antimicrobial susceptibility testing was performed by modified Kirby Bauer method. All gram negative organisms were further tested for ESBL and MBL production. Results:Of 451 isolates, 353 (78.2%) were gram negative and 98 (21.7%) were gram positive cocci. The most frequent infections were lower respiratory tract infections (32.9%). The most frequently isolated organisms were P. aeruginosa (20.1%) and Staphylococcus epidermidis (8.6%). Higher resistance (60-100%) was observed to amoxycillin, ceftazidime, amoxyclav, ciprofloxacin and cotrimoxazole. ESBLs production was found in (45.3%) isolates. 75.0% of Staphylococcus aureus and 20.5% of S.epidermidiswere MRSA positive. 85.7% showed MBL production. Conclusion: Surveillance of antibiotic susceptibility patterns of predominant bacteria is necessary to monitor changes in susceptibility patterns and to guide the clinician in choosing empirical or directed therapy appropriately, especially in ICU setting. KEYWORDS: Intensive Care Unit; Antibiotic resistance; MRSA.